Developing computer information security technology and ways to prevent problems from occurring - Abdulssalam Jomah Akroma; Fatimah Allafi Abdullah Isdayrah (المجلة الأفروآسيوية للبحث العلمي, 2024)
Computer technology and networks have advanced quickly due to social growth, and from being "rare" to "universal," they are now. However, the ensuing security instability has also grown to be a significant issue when it comes to evaluating people and society. Thus, to construct a computer system quickly and steadily, it is now necessary to investigate and research the challenging issue of how to strengthen computer security defence capabilities. To support the governance business, this paper first examines the fundamentals of information security, clarifies associated problems, and offers recommendations for preventative and measurement techniques based on real-world circumstances.